Christian Spiritual Formation towards Holiness - Pavel Hanes; Dana Hanesová (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Freedom is one of the most fervently fought for values and, at the same time, the very idea of freedom belongs to concepts that are essentially contested. This situation is a part of human brokenness, and in Christian formation, it has to be seriously dealt with. According to the popular view, ‘holiness’ is a life-negating and judgmental attitude towards everything ‘normal.’ In biblical usage, it connotes belonging to God as a gift in Christ. Spiritual formation begins with a biblical explanation of freedom and holiness. A Christian worldview has to be the background to Christian formation, functioning as a correction of the commonly- accepted naturalistic worldview. A personal experiential relationship with God is the key to successful growth towards realistic and practical holiness in daily life. ‘Dos and don’ts’ that usually arise at the beginning of religious education shall be experienced as liberating instructions, if they are offered as guidance to a fully persuaded mind and a devotedly loving heart.